2021
DOI: 10.3390/su13105451
|View full text |Cite
|
Sign up to set email alerts
|

Towards Sustainability in Air Traffic Management

Abstract: The International Civil Aviation Organization is estimated that the number of domestic and international passengers will be expected to reach six billion by 2030. This exponential growth in air transport has resulted in a wide range of adverse effects such as environmental impacts. The purpose of this research is to develop new air traffic management, and operator (pilots, air traffic controllers) load measuring systems in order to save fuel, and flight time, thereby reducing environmental impact, carbon emiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
0
5
0
1
Order By: Relevance
“…There is insufficient data regarding the prevalence and impact of airport pollutants on the environment [73][74][75][76]. In European or Polish regulations, there are no specific provisions regarding the necessity of the determination or removal of benzotriazoles from runoff water generated upon the use of de-icing agents for airports [7,75,76].…”
Section: The Ecotoxicological Risk Of Btsmentioning
confidence: 99%
“…There is insufficient data regarding the prevalence and impact of airport pollutants on the environment [73][74][75][76]. In European or Polish regulations, there are no specific provisions regarding the necessity of the determination or removal of benzotriazoles from runoff water generated upon the use of de-icing agents for airports [7,75,76].…”
Section: The Ecotoxicological Risk Of Btsmentioning
confidence: 99%
“…Finally, the number of domestic and international air passengers will reach six billion by 2030, leading to negative impacts, such as on the environment. The goal is to develop new air traffic management and load measurement systems for operators to reduce environmental impacts, carbon emissions, greenhouse gas emissions, noise pollution, and operating costs [29]. In the United Kingdom, privatised utilities and infrastructure providers have increased labour productivity, lowered prices, improved service quality, and significantly contributed to public finances.…”
Section: Airline Industrymentioning
confidence: 99%
“…Therefore, in such risk topics, relevant personnel need to focus on improving their professional skills and concentration to avoid similar events. At the same time, there were also some risk topics that involved the operating conditions of airspace when incidents occurred, airspace structure, or operating rules/procedures [32], etc. From these topics, it was found that unreasonable airspace structure and cumbersome operating rules/procedures would affect the safety of ATC operations.…”
Section: Lda Topic Discoverymentioning
confidence: 99%